The rs1468615 T>C in ABCB4 confers protection against gallstone disease but not against severe liver disease. (March 2023) - Tavaglione, F.; Jamialahmadi, O.; De Vincentis, A.; Gallo, P.; Incalzi, R. Antonelli; Picardi, A.; Romeo, S.; Vespasiani-Gentilucci, U.
Abstract : Background: Growing evidence suggests that cholestatic and fatty liver disease share common pathophysiological mechanisms. Rare loss-of-function variants in the ATP binding cassette subfamily B member 4 ( ABCB4 ) gene have been associated with gallstone disease and with a spectrum of cholestatic liver diseases, ranging from progressive familial intrahepatic cholestasis to less severe conditions, like low phospholipid-associated cholelithiasis or intrahepatic cholestasis during pregnancy. Whole-genome sequencing of Icelanders revealed the common variant rs2109505 T>A in ABCB4, conferring protection against gallstone disease and being associated with lower transaminases. Aim: To identify common variants in ABCB4 associated with severe liver disease. Methods: We examined the association of missense and nonsense common variants (minor allele frequency >1%) at the ABCB4 locus with ALT in 412, 912 Europeans from the UK Biobank using a whole-genome regression model. Next, we tested the association of the lead variant in the region with liver-related traits and incident severe liver disease in a subset of 365, 449 unrelated Europeans by multiple linear/logistic regression models and Cox proportional hazards models, respectively. Analyses were adjusted for age, gender, BMI, type 2 diabetes, alcohol intake, and first 10 PCs of ancestry. Results: We identified the ABCB4 rs1468615 T>C as the lead variant independently associated with ALT ( P  = 2.26 × 10 −34 ). The rs1468615 is an intronic variant in high linkage disequilibrium with the rs2109505 (r 2  = 0.94). The rs1468615 was associated with lower risk of gallstone disease ( P  = 8.56 × 10 −12 ) and with lower liver enzymes ( P  = 2.28 × 10 −30, P  = 8.31 × 10 −09, and P  = 8.08 × 10 −04 for ALT, AST, and GGT respectively). No association was found with liver cirrhosis, liver cancer, and gallbladder/biliary tract cancer. No association was found with incident severe liver disease. Conclusions: The rs1468615 T>C in ABCB4 confers protection against gallstone disease but not against the development of severe liver disease.